Agricultural Growth in Sub-Saharan African Countries and China - Khan, Mahmood (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1995)
Agriculture remains the dominant sector in the economies of most Sub-Saharan African countries. However, the experience of agricultural growth in the region stands in sharp contrast to the robust performance of agriculture in many Asian countries, particularly China. In a number of African countries, labor productivity has fallen and land productivity has not risen significantly. In China, on the other hand, land and labor productivities have increased steadily over the past two decades. An examination of factors underlying the contrasting experiences of China and countries in Sub-Saharan Africa reveals important differences in the institutional and policy environments affecting the use of new and profitable technologies to raise land and labor productivities.